2018
DOI: 10.1039/c8sm00998h
|View full text |Cite
|
Sign up to set email alerts
|

The effect of linker DNA on the structure and interaction of nucleosome core particles

Abstract: In eukaryotes, the compaction of chromatin fibers composed of nucleosome core particles (NCPs) connected by a linker DNA into chromosomes is highly efficient; however, the underlying folding mechanisms remain elusive. We used small angle X-ray scattering (SAXS) to investigate the influence of linker DNA length on the local structure and the interparticle interactions of the NCPs. In the presence of the linker DNA of 30 bp or less in length, the results suggest partial unwrapping of nucleosomal DNA on the NCP i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
5
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 82 publications
(88 reference statements)
3
5
0
3
Order By: Relevance
“…The lower intensity in that area may be caused by more flexible linker DNA arms in solution compared to the crystal and Cryo-EM structures, which results in the transient unwrapping of DNA. DNA unwrapping from the HO was demonstrated to produce a comparable effect on the SAXS spectrum 40 and observed in solutions of NCPs with tailless H3 and H4 39 . The increased values of R g and D max from the SAXS study suggest dynamic differences in the structure of the chromatosome compared to the nucleosome, and the result indicates an influence of the linker histone as a structural factor in linker DNA compaction of the nucleosome.…”
Section: Resultsmentioning
confidence: 72%
See 2 more Smart Citations
“…The lower intensity in that area may be caused by more flexible linker DNA arms in solution compared to the crystal and Cryo-EM structures, which results in the transient unwrapping of DNA. DNA unwrapping from the HO was demonstrated to produce a comparable effect on the SAXS spectrum 40 and observed in solutions of NCPs with tailless H3 and H4 39 . The increased values of R g and D max from the SAXS study suggest dynamic differences in the structure of the chromatosome compared to the nucleosome, and the result indicates an influence of the linker histone as a structural factor in linker DNA compaction of the nucleosome.…”
Section: Resultsmentioning
confidence: 72%
“…R g values calculated from the distance distribution function P(r), from SAXS data for the 147 bp NCP, were previously reported to be around 42 Å in low salt conditions 36,40,41 . The R g values of the 177 bp nucleosome (47.6 Å) and the chromatosome (49.4 Å) found in this work (Table S1) are more significant due to the presence of linker DNA, and linker histone, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This conclusion was also supported by dynamic light scattering investigations, which displayed a larger hydrodynamic diameter for Telo-NCP in comparison with 601-NCP (data not shown). Earlier works have shown that the depth of the dip in the NCP SAXS spectrum at 0.14 Å -1 is sensitive to DNA unwrapping (71)(72)(73)(74). The NCP at low concentration (1-2.5 mg/mL) in low salt buffer (10 mM KCl) exhibit minimal inter-particle interactions, thereby facilitating the study of the form factor of the NCP SAXS spectrum (52).…”
Section: The Telo-ncp Exhibits a Stable Yet Dynamic Structure In Solumentioning
confidence: 99%
“…В настоящее время значительная часть таких исследований выполняется на корнуклеосомах, не имеющих линкерных участков ДНК (линкеров) [1,6,7]. В других случаях изучаемые нуклеосомы имеют линкеры (один или два), а их длина изменяется в широких пределах [1,2,4,5,8]. При столь широкой вариабельности используемых мононуклеосом возникают вопросы о возможной зависимости результатов изучения молекулярных взаимодействий от наличия, числа и длины линкеров, а также о правомерности прямого сравнения данных, полученных в различных исследованиях.…”
unclassified